Investigation of tolerance of sorghum crop to water deficit conditions during drip irrigation - Sobitjonov Jasurbek Jaloliddin o’g’li; Nasibov Boburbek Rustamjon o’g’li (Zien Journals, 2023)
In the article, the sorghum plant was irrigated using modern irrigation technologies and the irrigation period of the plant as a result of drip irrigation was studied. In the article, the soil moisture determination in the research area, the information of the area for planting sorghum was studied. Phenological observations were made and the results were analyzed. The resistance of the sorghum crop to water shortage conditions during the period of drip irrigation was checked. During the research, land reclamation conditions were studied, seed planting plans were made based on the data for plant growth. Monitoring wells were dug to monitor the level of underground water and permanent monitoring was established. Based on the results of drip irrigation, the yield of the crop was determined, according to which the average weight of a head was 0.10 kg, and the average weight of 30 heads was 3.1 kg. "Using watersaving technologies" of the "Tashkent Institute of Irrigation and Agricultural Mechanization Engineers" National Research University scientific training center located in Ortachirchik district of Tashkent region in 2022 in order to check the resistance of agricultural crops to water shortage conditions during the irrigation period prepared based on the results of scientific research carried out at the landfill.
Keywords: Sorghum; drip irrigation; productivity